A low-alloy high-strength steel bar for railway tunnel and a preparation method thereof
Patent Information
- Application Number
- CN202611312048.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-10-27
AI Technical Summary
该类钢筋成分体系中耐蚀合金元素不足,在高浓度H2S、Cl-、SO42-共存环境中均匀腐蚀速率高达0.2~0.5mm/a,局部点蚀深度超过1mm/a,服役寿命不足10年;同时钢质纯净度低,P、S等有害杂质元素含量偏高,易在晶界偏聚形成薄弱区并作为氢陷阱促进氢原子富集,在地应力与硫化氢协同作用下极易发生SCC与HE耦合断裂
[0088]本发明首创铁路隧道专用Ni-Cr-Cu-Nb-V五元协同低合金成分体系,通过1.45%~1.55%的Ni、1.95%~2.05%的Cr、0.20%~0.30%的Cu主耐蚀元素协同作用,抑制阳极溶解;同时配合0.04%~0.06%的Nb和0.07%~0.08%的V微合金元素,形成不可逆氢陷阱以抑制氢致开裂。在上述成分体系的协同作用下,本发明钢筋在H2S、Cl-、SO42-共存环境中能够形成致密、稳定且附着力强的腐蚀产物膜,有效阻挡侵蚀性离子向基体渗透,均匀腐蚀速率降低至0.05mm/a以下,局部点蚀深度控制在0.1mm/a以内,满足铁路隧道100年耐久性设计要求;同时实现了阳极溶解与氢致开裂两种失效模式的同步阻断,在高地应力与高浓度硫化氢协同作用下,应力腐蚀敏感性降低80%以上,杜绝了无预兆脆性断裂事故的发生。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0002] This invention belongs to the field of steel materials technology, specifically relating to a low-alloy high-strength steel bar for railway tunnels resistant to hydrogen sulfide stress corrosion and its preparation method. Background Technology
[0003] As my country's railway construction accelerates its extension into the western mountainous and plateau regions, numerous deep-buried long tunnels have emerged in major national railway projects such as the Sichuan-Tibet Railway, Chongqing-Kunming High-Speed Railway, Xi'an-Ankang High-Speed Railway, and Chengdu-Dazhou-Wanzhou High-Speed Railway. These deep-buried tunnels generally face extreme geological environments characterized by "three highs": high ground stress, high hydrogen sulfide concentration (with some tunnels having H2S levels as high as 10,000 ppm), and high chloride ion content (groundwater chloride content is extremely high). - Concentrations can reach 1000 mg / L, accompanied by SO4. 2- HCO3 - Corrosive ions coexist. Railway tunnels are projects designed for a century, with a minimum design life of 100 years for their support structures. However, under these extreme environments, the durability of traditional support materials faces severe challenges.
[0004] Reinforcing steel bars are the core load-bearing material in tunnel shotcrete support, lining structures, and anchor bolt support systems, and their service performance directly determines the overall safety of the tunnel structure. In high-hydrogen sulfide railway tunnel environments, the failure of reinforcing steel bars is an environmental fracture process resulting from the combined effects of corrosive media and mechanical stress. First, hydrogen sulfide dissolves in groundwater to form a weakly acidic corrosive medium, which reacts with the reinforcing steel matrix to generate a loose and porous FeS corrosion product film, which cannot block Cl... - SO4 2- First, the penetration of corrosive ions accelerates uniform corrosion and localized pitting corrosion. Second, a large number of hydrogen atoms are generated during hydrogen sulfide corrosion. These hydrogen atoms penetrate into the interior of the steel bars and accumulate in stress concentration areas, inducing hydrogen-induced cracking (HE). Third, the continuous tensile stress generated by the high ground stress in the tunnel is coupled with the corrosion effect, triggering stress corrosion cracking (SCC), which manifests as brittle fracture without warning. Its fracture strength is only 30% to 50% of the material's ultimate strength.
[0005] Currently, HRB400E and HRB500E ordinary hot-rolled ribbed steel bars, as specified in GB / T 33953, are commonly used in tunnel engineering. Their typical composition is: C≤0.21%, Si≤0.80%, Mn≤1.60%, P≤0.030%, S≤0.030%. This type of steel bar composition lacks corrosion-resistant alloying elements, which can lead to corrosion problems under high concentrations of H2S and Cl. - SO4 2-In the coexisting environment, the uniform corrosion rate is as high as 0.2~0.5 mm / a, the local pitting depth exceeds 1 mm / a, and the service life is less than 10 years. At the same time, the steel has low purity and high content of harmful impurity elements such as P and S. It is easy to agglomerate at the grain boundary to form weak areas and act as a hydrogen trap to promote the enrichment of hydrogen atoms. Under the combined effect of geostress and hydrogen sulfide, SCC and HE coupling fracture are very likely to occur.
[0006] It is worth noting that some existing corrosion-resistant steel reinforcement technologies (such as CN119685722A) are mainly designed for chloride ion corrosion environments, and their core failure mode is the thinning of the steel reinforcement cross-section caused by electrochemical corrosion. However, the failure of steel reinforcement in the high hydrogen sulfide environment of railway tunnels is an environmental fracture process caused by the synergistic effect of corrosive media and mechanical stress, involving two parallel failure modes: anodic dissolution and hydrogen-induced cracking. The failure mechanisms of the two are completely different—the former can be suppressed by increasing the Cr and Cu content to form a dense rust layer, while the latter requires irreversible hydrogen trapping to capture diffusing hydrogen atoms. Therefore, the composition system of corrosion-resistant steel reinforcement designed for chloride ion corrosion cannot be directly transferred to the hydrogen sulfide stress corrosion scenario; the technical problems and solutions faced by the two are fundamentally different.
[0007] Some projects have attempted to use stainless steel reinforcing bars (such as 304, 316L, or 2205 duplex stainless steel), which form a passivation film through high Cr (16%~26%) and high Ni (8%~22%) alloying to improve corrosion resistance. However, their yield strength is only about 205 MPa (304 stainless steel), which cannot meet the high strength requirements of support materials under high ground stress in deep-buried tunnels; moreover, the cost is 5 to 10 times that of ordinary reinforcing bars, making large-scale application in railway tunnel projects impossible. In addition, surface-protected corrosion-resistant reinforcing bars (such as hot-dip galvanized steel, epoxy resin coating, etc.) rely on external protective layers to isolate corrosive media, but these protective layers are easily damaged during transportation and installation. Damaged areas will form "large cathode-small anode" corrosion cells, accelerating localized corrosion; and the lifespan of the protective layer is limited (epoxy resin coating about 20 to 30 years, galvanized layer about 10 to 15 years), far below the 100-year design life requirement for railway tunnels.
[0008] In summary, existing ordinary hot-rolled steel bars, stainless steel bars, and surface-protected corrosion-resistant steel bars cannot simultaneously meet the triple requirements of high-hydrogen sulfide railway tunnels: high strength (≥500MPa), high toughness (elongation after fracture ≥18%, impact energy at -20℃ ≥40J), and high resistance to hydrogen sulfide stress corrosion. They also cannot fundamentally suppress both anodic dissolution and hydrogen-induced cracking, the two core failure modes. Therefore, there is an urgent need to develop a low-alloy steel bar that, based on the fundamental properties of the matrix, combines high strength, high toughness, and excellent resistance to hydrogen sulfide stress corrosion to adapt to the extreme service conditions of railway tunnels and meet the 100-year design life requirement. Summary of the Invention
[0009] This invention provides a low-alloy high-strength steel bar for railway tunnels resistant to hydrogen sulfide stress corrosion and its preparation method. The invention utilizes a pioneering Ni-Cr-Cu-Nb-V five-element synergistic low-alloy composition system. The main corrosion-resistant elements, 1.45%~1.55% Ni, 1.95%~2.05% Cr, and 0.20%~0.30% Cu, inhibit anodic dissolution. Combined with 0.04%~0.06% Nb and 0.07%~0.08% V microalloying elements, an irreversible hydrogen trap is formed to inhibit hydrogen-induced cracking, achieving simultaneous blocking of both anodic dissolution and hydrogen-induced cracking failure modes. Simultaneously, strict steel purification smelting is employed, controlling P to ≤0.015% and S to ≤0.010%. This process eliminates the segregation of harmful impurities at grain boundaries and reduces harmful hydrogen traps at the metallurgical source. Furthermore, the microstructure is optimized through a composite preparation process of "two-stage controlled rolling and cooling + 820℃ normalizing," resulting in a steel bar yield strength ≥500MPa, tensile strength ≥630MPa, elongation after fracture ≥18%, and impact absorption energy at -20℃ ≥40J. The uniform corrosion rate is reduced to below 0.05mm / a, and stress corrosion sensitivity is reduced by more than 80%, meeting the 100-year durability design requirements for railway tunnels. Moreover, the overall cost is only about 1 / 5 of that of stainless steel steel bars. It combines high strength, high toughness, and high resistance to hydrogen sulfide stress corrosion, fully adapting to the extreme service conditions of high ground stress, high hydrogen sulfide, and high chloride ion levels in deeply buried tunnels.
[0010] The technical solution of the present invention is as follows:
[0011] On one hand, the present invention provides a low-alloy high-strength steel bar for railway tunnels resistant to hydrogen sulfide stress corrosion, which is composed of the following chemical components by weight percentage:
[0012] C: 0.09%~0.14%;
[0013] Si: 0.25%~0.40%;
[0014] Mn: 0.80%~0.90%;
[0015] P: ≤0.015%;
[0016] S: ≤0.010%;
[0017] Cr: 1.95%~2.05%;
[0018] Ni: 1.45%~1.55%;
[0019] Cu: 0.20%~0.30%;
[0020] V: 0.07%~0.08%;
[0021] Nb: 0.04%~0.06%;
[0022] Al: 0.02%~0.05%;
[0023] The balance consists of Fe and unavoidable impurities.
[0024] Preferably, the content of C is 0.10%~0.13%;
[0025] Preferably, the Si content is 0.30%~0.35%;
[0026] Preferably, the Mn content is 0.82%~0.88%;
[0027] Preferably, the content of P is ≤0.012%;
[0028] Preferably, the content of sulfur is ≤0.008%;
[0029] Preferably, the Cr content is 1.98%~2.02%;
[0030] Preferably, the Ni content is 1.48%~1.52%;
[0031] Preferably, the Cu content is 0.23%~0.27%;
[0032] Preferably, the content of V is 0.072%~0.078%;
[0033] Preferably, the Nb content is 0.045%~0.055%;
[0034] Preferably, the Al content is 0.030%~0.045%.
[0035] More preferably, the content of C is 0.11%~0.12%;
[0036] More preferably, the Si content is 0.32%~0.33%;
[0037] More preferably, the Mn content is 0.84%~0.86%;
[0038] More preferably, the content of P is ≤0.010%;
[0039] More preferably, the content of S is ≤0.006%;
[0040] More preferably, the Cr content is 1.99%~2.01%;
[0041] More preferably, the Ni content is 1.49%~1.51%;
[0042] More preferably, the Cu content is 0.24%~0.26%;
[0043] More preferably, the content of V is 0.074%~0.076%;
[0044] More preferably, the Nb content is 0.048%~0.052%;
[0045] More preferably, the Al content is 0.032%~0.038%.
[0046] Preferably, the low-alloy high-strength steel bars for railway tunnels that are resistant to hydrogen sulfide stress corrosion have a uniform and fine ferrite-pearlite structure, wherein the average grain size of the ferrite is 4 to 8 μm, the volume fraction of ferrite is 80% to 88%, and the remainder is dispersed lamellar pearlite.
[0047] More preferably, corresponding to the median composition and optimal process window of the present invention, the average grain size of ferrite is 5 to 6 μm and the volume fraction of ferrite is 83% to 85%.
[0048] Preferably, the microstructure is obtained through controlled rolling and cooling followed by normalizing.
[0049] Preferably, the reinforcing bars are used in shotcrete support, lining structures, or anchor support systems in railway tunnels with high hydrogen sulfide environments (H2S concentration ≥ 1000 ppm).
[0050] The functions of the above-mentioned elements in this invention are explained as follows:
[0051] (1) Main corrosion-resistant elements: Ni-Cr-Cu synergistically inhibits anodic dissolution
[0052] Ni (1.45~1.55%): A thermodynamically stable element and the most effective element against hydrogen sulfide stress corrosion. On the one hand, it promotes the formation of fine and dense α-FeOOH and NiFe2O4 spinel phases in the corrosion product layer, significantly improving the density and adhesion of the rust layer; on the other hand, it gives the inner rust layer cation selectivity, effectively blocking Cl. - HS - Anions penetrate into the matrix, thereby increasing the matrix's self-corrosion potential and reducing its electrochemical activity.
[0053] Cr (1.95~2.05%): An accelerating film-forming element, it synergistically forms Fe-Cr-Ni composite oxides with Fe and Ni, filling the pores and cracks in the corrosion product film and further enhancing the protective properties of the rust layer; when the Cr content reaches 2%, it can effectively inhibit Cl... - It penetrates the rust layer to reach the substrate surface, significantly reducing pitting corrosion susceptibility.
[0054] Cu (0.20~0.30%): During corrosion, it accumulates in the inner layer of the rust layer, forming stable compounds such as Cu2S and CuO, which inhibit the cathodic reaction of hydrogen sulfide corrosion; in synergy with Ni and Cr, it can reduce the uniform corrosion rate by more than 60%.
[0055] Al (0.02%–0.05%): A strong deoxidizing and grain-refining element, it enhances steel purity and optimizes microstructure. On one hand, as a final deoxidizer, it deeply removes dissolved oxygen from molten steel, reducing oxide inclusions and pitting corrosion initiation sites and harmful hydrogen traps. Combined with low-P and low-S purification design, it reduces the risk of localized corrosion and hydrogen-induced cracking from the metallurgical source. On the other hand, it combines with nitrogen in the steel to form dispersed nano-AlN particles, which pin grain boundaries and inhibit austenite grain growth during rolling and normalizing. Combined with a two-stage controlled rolling and cooling process, it further refines ferrite grains, simultaneously improving the strength and low-temperature impact toughness of the reinforcing steel, while also improving grain boundary conditions and reducing the tendency for stress corrosion grain boundary cracking. Controlling the Al content within the reasonable range of 0.02%–0.05% avoids coarse oxide inclusions and surface quality problems in continuously cast billets caused by excessive Al, ensuring the uniformity of the reinforcing steel's microstructure and its adaptability to on-site welding construction in tunnels.
[0056] (2) Microalloying elements: Nb-V composite inhibits hydrogen-induced cracking
[0057] Nb (0.04~0.06%): A strong carbide-forming element that precipitates nano-sized NbC particles in steel. These particles act as irreversible hydrogen traps, capturing hydrogen atoms and preventing hydrogen from diffusing and accumulating in stress concentration areas. At the same time, they refine grains, improve grain boundary bonding, and reduce the susceptibility to hydrogen-induced cracking.
[0058] V (0.07~0.08%): Co-precipitates VC and V (C, N) particles with Nb, increasing the hydrogen trap density; at the same time, it strengthens the steel bars through precipitation, compensating for the strength loss caused by low-carbon design.
[0059] (3) Control of matrix elements and impurities
[0060] C (0.09~0.14%): Low-carbon design reduces cementite precipitation and lowers the rate of hydrogen evolution reaction at the cathode; at the same time, it improves welding performance and toughness.
[0061] Si (0.25~0.40%), Mn (0.80~0.90%): Ensure basic strength and deoxidation effect, and avoid the decrease in toughness and increase in corrosion sensitivity caused by excessive content.
[0062] P≤0.015%, S≤0.010%: Strictly control the content of harmful impurity elements, eliminate the segregation of P and S at grain boundaries, reduce intergranular corrosion and harmful hydrogen traps, and reduce the risk of environmental fracture from the metallurgical source.
[0063] The reinforcing steel of this invention is a hot-rolled ribbed steel bar with continuous crescent-shaped transverse ribs on the surface, and the height of the transverse ribs is ≥0.06d. The diameter of the reinforcing steel bar ranges from 12 to 32 mm, which can meet the stress requirements of different parts of tunnel support.
[0064] The mechanical properties of the reinforcing steel bars of this invention fully meet and exceed the national standard requirements for HRB500E reinforcing steel bars.
[0065]
[0066] The corrosion resistance performance of this invention was tested in a simulated high-hydrogen sulfide environment in a railway tunnel (pH=5, containing 0.25 g / L NaCl, 0.1 g / L KNO3, 0.5 g / L Na2SO4, 1 g / L NaHCO3, and 1 g / L NaHSO3). The results are as follows: Uniform corrosion rate: ≤0.04 mm / a (0.3~0.4 mm / a for ordinary HRB500E steel bars); Local pitting depth after 60 days of immersion: ≤0.08 mm (0.8~1.0 mm for ordinary HRB500E steel bars); Slow strain rate tensile test (SSRT) stress corrosion sensitivity: at open circuit potential (OCP): Iδ≤0.2%, Iψ≤1.6% (Iδ=7.3%, Iψ=25.2% for ordinary HRB500E steel bars); Hydrogen charging potential (-1200 mV). Under (vsSCE): Iδ≤30%, Iψ≤46% (for ordinary HRB500E steel bars, Iδ=27.1%, Iψ=58.3%).
[0067] On the other hand, the present invention provides a method for preparing the above-mentioned low-alloy high-strength steel bars for railway tunnels resistant to hydrogen sulfide stress corrosion, the method comprising the following steps performed sequentially:
[0068] (1) Purification smelting process;
[0069] (2) Continuous casting process;
[0070] (3) Controlled rolling and controlled cooling process;
[0071] (4) Normalizing heat treatment process.
[0072] Preferably, the purification smelting process includes:
[0073] Hot metal pretreatment: Desulfurization and dephosphorization processes are adopted to ensure that S ≤ 0.005% and P ≤ 0.010% in the hot metal;
[0074] Converter steelmaking: final control C ≥ 0.06% to avoid over-oxidation, slag-blocking tapping is adopted, and slag layer thickness ≤ 50mm;
[0075] LF furnace refining: white slag holding time ≥15min, adjust alloy element composition to the target range;
[0076] RH vacuum degassing: vacuum degree ≤67Pa, holding time ≥10min, so that [H]≤1.5ppm, [O]≤20ppm, and [N]≤40ppm in steel.
[0077] Preferably, in the continuous casting process, full-process protective casting is adopted to prevent secondary oxidation; electromagnetic stirring in the crystallizer and electromagnetic stirring at the end are adopted; the cross-section of the billet is 150mm×150mm; the casting speed is 2.0~2.5m / min; the secondary cooling zone adopts a weak cooling process; and the specific water content is 0.8~1.0L / kg.
[0078] Preferably, the controlled rolling and controlled cooling process includes:
[0079] The steel billet is heated to 1150–1200℃ and held for 1.5–2.0 hours.
[0080] The rolling process employs a two-stage controlled rolling process: roughing and finishing. In the roughing stage, the initial rolling temperature is 1050–1100℃, the final rolling temperature is 950–1000℃, and the cumulative reduction rate is ≥60%. In the finishing stage, the initial rolling temperature is 850–900℃, the final rolling temperature is 800–850℃, and the cumulative reduction rate is ≥70%.
[0081] After rolling, controlled cooling is performed using water cooling at a rate of 10–15 °C / s, with a final cooling temperature of 600–650 °C, followed by air cooling to room temperature.
[0082] Preferably, in the normalizing heat treatment process, the heating temperature is 820±10℃, the holding time is 1 hour, and the holding time is increased by 0.5 hours for every 10mm increase in the diameter of the reinforcing bar. The heating rate is <50℃ / hour, and the bar is air-cooled to room temperature after being removed from the furnace. Normalizing treatment can eliminate the internal stress generated during rolling, refine the grains, obtain a uniform and fine ferrite-pearlite structure, significantly improve the elongation and impact toughness of the reinforcing bar, while maintaining high strength and corrosion resistance.
[0083] This invention fundamentally solves the failure problem of existing steel bars in high hydrogen sulfide railway tunnel environments through an integrated design of composition, process, microstructure, and properties.
[0084] Composition Design: This invention adopts a Ni-Cr-Cu main corrosion-resistant element system to form a double-layer dense corrosion product film on the surface of the steel reinforcement, consisting of an outer layer of FeS and an inner layer of NiFe2O4-Cr2O3-Cu2S, which effectively blocks the penetration of corrosive ions and inhibits anodic dissolution. At the same time, Nb-V microalloying elements are added to form nanoscale carbide hydrogen traps, which capture hydrogen atoms and prevent hydrogen-induced cracking, thereby achieving simultaneous suppression of the two core failure modes of anodic dissolution and hydrogen-induced cracking.
[0085] Process Design: This invention strictly controls the content of harmful impurities and gases such as P and S through purification smelting, eliminates weak grain boundary areas and harmful hydrogen traps, and reduces corrosion and hydrogen embrittlement sensitivity from the metallurgical source; it adopts controlled rolling and controlled cooling process to obtain a refined ferrite-pearlite structure to ensure basic strength; and it further refines the grains and eliminates internal stress through 820℃ normalizing treatment, which significantly improves elongation and impact toughness, and solves the problem of the imbalance between strength and toughness of existing corrosion-resistant steel bars.
[0086] Synergistic performance: The low-carbon design of this invention ensures good toughness and weldability, Nb-V precipitation strengthening compensates for the strength loss caused by low carbon, and Ni-Cr-Cu alloying provides excellent corrosion resistance. The three work together to achieve a perfect balance of high strength, high toughness and high resistance to hydrogen sulfide stress corrosion, meeting the requirements for a century of service for railway tunnels.
[0087] Compared with the prior art, the present invention has the following beneficial effects:
[0088] This invention pioneers a Ni-Cr-Cu-Nb-V synergistic low-alloy composition system specifically for railway tunnels. Through the synergistic effect of 1.45%~1.55% Ni, 1.95%~2.05% Cr, and 0.20%~0.30% Cu as the main corrosion-resistant elements, anodic dissolution is inhibited. Simultaneously, the addition of 0.04%~0.06% Nb and 0.07%~0.08% V microalloying elements forms irreversible hydrogen traps to suppress hydrogen-induced cracking. Under the synergistic effect of the above composition system, the steel reinforcement of this invention exhibits excellent corrosion resistance against H2S and Cl-. - SO4 2- In the coexisting environment, a dense, stable and strongly adherent corrosion product film can be formed, effectively blocking the penetration of corrosive ions into the substrate. The uniform corrosion rate is reduced to below 0.05 mm / a, and the local pitting depth is controlled within 0.1 mm / a, meeting the 100-year durability design requirements of railway tunnels. At the same time, it achieves the simultaneous blocking of two failure modes: anodic dissolution and hydrogen-induced cracking. Under the synergistic effect of high ground stress and high concentration of hydrogen sulfide, the stress corrosion sensitivity is reduced by more than 80%, eliminating the occurrence of brittle fracture accidents without warning.
[0089] This invention, through rigorous steel purification smelting, controls the P content to ≤0.015% and the S content to ≤0.010%, eliminating the segregation of harmful impurities at grain boundaries from the metallurgical source, reducing weak areas of intergranular corrosion and harmful hydrogen traps, significantly reducing the risk of intergranular corrosion and hydrogen-induced cracking, and further improving the structural integrity and long-term safety of steel bars in extreme environments.
[0090] This invention employs a composite preparation process of "two-stage controlled rolling and cooling + 820℃ normalizing". The grains are refined through two-stage controlled rolling of roughing and finishing, followed by a normalizing process of holding at 820℃ for 1 hour and air cooling to eliminate rolling internal stress and optimize the ferrite-pearlite microstructure. While ensuring excellent corrosion resistance, the steel bars achieve a yield strength ≥500MPa, tensile strength ≥630MPa, elongation after fracture ≥18%, and impact absorption energy ≥40J at -20℃. This achieves synergistic optimization of high strength, high toughness, and high resistance to hydrogen sulfide stress corrosion. It meets the high strength requirements of high ground stress in deep-buried tunnels and adapts to the high toughness requirements of large deformation of surrounding rock and low temperature at high altitudes, solving the core problem of the imbalance between strength and toughness in existing technologies.
[0091] All preparation steps of this invention are fully compatible with existing ordinary hot-rolled steel bar production lines, requiring no additional large-scale special equipment, enabling large-scale continuous production. The overall cost is only about 1 / 5 of that of stainless steel bars, demonstrating good economic efficiency and promising prospects for widespread application.
[0092] Furthermore, the alloy design of this invention differs fundamentally from existing corrosion-resistant steel reinforcement technology, resulting in several unexpected technical effects:
[0093] This invention abandons the existing high-Cr, low-Ni, and Nb-free solutions for chloride-resistant alloys, instead employing a "medium-Cr, high-Ni, Nb-V hydrogen trap" approach. This increases the Ni content to over 1.45%, which not only improves corrosion resistance but also promotes the formation of the NiFe2O4 spinel phase in the inner rust layer, imparting cation selectivity to the rust layer to block H₂S. - It penetrates and simultaneously increases the self-corrosion potential of the matrix through high Ni content.
[0094] This application uses a high Cr content, resulting in a dense and continuous underlying rust layer, which effectively inhibits Cl. - penetrate.
[0095] This invention also abandons the existing approach of compensating for corrosion resistance loss caused by low Cr / Ni with high Si, instead adopting a "low Si, high Ni" approach. High Si severely deteriorates weldability and toughness, which is unacceptable in on-site tunnel welding. This invention ensures corrosion resistance with high Ni while maintaining low Si to guarantee weldability, achieving simultaneous optimization of corrosion resistance and weldability. It is precisely this approach that has resulted in several unexpected technical effects:
[0096] First, in Example 1 of this application, the elongation loss rate Iδ at open circuit potential is only 0.15%, and the reduction of area loss rate Iψ is only 1.2%, which is more than 80% and more than 50% lower than that of ordinary HRB500E (Iδ=7.3%, Iψ=25.2%) and existing corrosion-resistant steel bars (Comparative Example 11, Iδ=3.5%, Iψ=12.0%), respectively. This magnitude of reduction cannot be expected by simply adding the elements together, but can only be achieved through the synergistic effect of the five elements Ni-Cr-Cu-Nb-V.
[0097] Second, in existing technologies, increasing strength usually requires increasing the carbon content or precipitation strengthening, but this increases the susceptibility to hydrogen-induced cracking. This invention compensates for the strength loss caused by low carbon content (0.09-0.14%) through Nb-V precipitation strengthening, while NbC / VC acts as an irreversible hydrogen trap to capture hydrogen atoms, achieving both strengthening and resistance to hydrogen embrittlement in the same precipitation process.
[0098] Third, the overall cost of this invention is only 1 / 5 of that of 304 stainless steel, but its stress corrosion resistance (Iδ≤0.2% at open circuit potential) is close to that of 304 stainless steel, and its yield strength (≥500MPa) is far superior to that of 304 stainless steel (about 205MPa), achieving a simultaneous breakthrough in high strength and high stress corrosion resistance.
[0099] definition
[0100] The "irreversible hydrogen trap" described in this invention is in contrast to reversible hydrogen traps such as dislocations and ordinary grain boundaries. Hydrogen atoms trapped in reversible hydrogen traps can still desorb and revert to diffuse hydrogen under normal service conditions, migrating to stress concentration sites and inducing hydrogen-induced cracking. Irreversible hydrogen traps, however, refer to microscopic sites where the binding energy between hydrogen atoms and the trap site is greater than 60 kJ / mol. At the actual service temperature of the steel reinforcement (normal temperature), hydrogen atoms cannot obtain sufficient desorption activation energy to escape from the trap. The trapped hydrogen atoms are fixed and no longer participate in the hydrogen diffusion behavior of the matrix. In this invention, the irreversible hydrogen traps mainly originate from the semi-coherent phase interfaces between nanoscale NbC and VC carbides formed by Nb and V precipitation and the ferrite matrix. These traps can capture hydrogen atoms generated during hydrogen sulfide corrosion, reducing the transport and enrichment of diffuse hydrogen to grain boundaries and stress concentration areas, thereby inhibiting hydrogen-induced cracking. Detailed Implementation
[0101] The present invention will be further described below with reference to embodiments and comparative examples, but the scope of protection of the present invention is not limited thereto.
[0102] Example
[0103] The nominal diameter of the reinforcing bars involved in the following examples and comparative examples is 20mm. All performance tests were completed on samples of the same batch and specification to ensure consistency in comparison.
[0104] I. Chemical Composition of the Test Steel
[0105] The chemical composition (mass fraction, wt%) of each embodiment and comparative example is shown in the table below, with the balance being Fe and unavoidable impurities:
[0106]
[0107] II. Preparation Process Description
[0108] 1. Examples 1-7 and Comparative Examples 1-7: all adopted the preparation process described in this invention, and the core parameters are as follows:
[0109] Purification smelting: hot metal pretreatment for desulfurization and dephosphorization → converter slag blocking and tapping → LF refining white slag holding for 18 min → RH vacuum degassing (vacuum degree ≤60Pa, holding for 12 min), finished product [H]≤1.2ppm, [O]≤15ppm;
[0110] Continuous casting: 150mm×150mm billet, casting speed 2.2m / min, secondary cooling water ratio 0.9L / kg, full-process protective casting;
[0111] Controlled rolling and cooling: heating temperature 1180℃ and holding temperature for 1.8h; roughing rolling: initial rolling at 1080℃ and final rolling at 980℃, with a cumulative reduction rate of 65%; finishing rolling: initial rolling at 880℃ and final rolling at 820℃, with a cumulative reduction rate of 75%; water cooling after rolling, cooling rate 12℃ / s, final cooling temperature 620℃, and air cooling to room temperature;
[0112] Normalizing treatment: heating temperature 820℃, holding time 1h, calculated by adding 0.5h for every 10mm increase in steel bar diameter, heating rate 40℃ / h, then air cooling after removal from the furnace.
[0113] 2. Comparative Example 8: The composition is the same as in Example 1, and the smelting, continuous casting, controlled rolling and controlled cooling processes are completely the same, without subsequent normalizing heat treatment.
[0114] 3. Comparative Examples 9-11: These are commercially available industrial steel bars prepared using conventional production processes based on corresponding standards or existing technologies.
[0115] III. Performance Testing Methods
[0116] 1. Mechanical properties: Conduct room temperature tensile tests according to GB / T 228.1 to measure yield strength, tensile strength, elongation after fracture, and total elongation at maximum force; conduct V-notch impact tests at -20℃ according to GB / T 229 to measure impact absorption energy.
[0117] 2. Microstructure: The average grain size and volume fraction of ferrite were characterized using metallographic microscopy and EBSD.
[0118] 3. Uniform corrosion and pitting corrosion: The uniform corrosion rate and maximum pitting depth were tested by immersing the equipment in a simulated high hydrogen sulfide environment in a railway tunnel (pH=5, containing 0.25g / L NaCl, 0.1g / L KNO3, 0.5g / L Na2SO4, 1g / L NaHCO3, and 1g / L NaHSO3) for 60 days.
[0119] 4. Hydrogen sulfide stress corrosion: Slow strain rate tensile test (SSRT) was used, with a strain rate of 1×10⁻⁶. -6 s -1 The stress corrosion susceptibility was characterized by the elongation loss rate Iδ and the reduction of area loss rate Iψ in the simulated solution.
[0120] IV. Test Results and Comparative Analysis
[0121] 1. Microstructure parameters
[0122]
[0123] It is evident that the composition and process of this invention can stably obtain a fine-grained structure of 4.5~6.5μm and a ferrite content of 80%~88%. Deviations from the composition or process will lead to grain coarsening and decreased microstructure uniformity.
[0124] 2. Comparison of mechanical properties
[0125]
[0126] Key conclusions:
[0127] All embodiments within the scope of this invention meet the requirements of yield strength ≥ 500 MPa, elongation after fracture ≥ 18%, and impact absorption energy ≥ 40 J, and are far superior to the national standard HRB500E.
[0128] The strength drops significantly when Nb and V microalloying is lacking (Comparative Example 6), failing to meet high strength requirements;
[0129] When P and S exceed the standard (Comparative Example 7), the toughness deteriorates sharply, and the impact absorption energy is lower than the design threshold.
[0130] When the normalizing process is removed (Comparative Example 8), the plasticity and toughness decrease significantly, failing to meet the requirements for high toughness and large deformation.
[0131] The yield strength of 304 stainless steel (Comparative Example 10) is only 210 MPa, which cannot meet the requirements for high ground stress bearing capacity.
[0132] 3. Comparison of resistance to hydrogen sulfide corrosion
[0133]
[0134] Key conclusions:
[0135] The embodiments of the present invention have a uniform corrosion rate of ≤0.04mm / a and a pitting depth of ≤0.08mm, which is an order of magnitude lower than that of ordinary HRB500E, meeting the requirement of 100-year durability;
[0136] When Cu is lacking (Comparative Example 1), Cr is insufficient (Comparative Example 3), and Ni is insufficient (Comparative Example 5), the corrosion rate and pitting depth both increase significantly, failing to meet the service requirements of high hydrogen sulfide environments, thus verifying the necessity of Cr-Ni-Cu ternary synergy.
[0137] When Cr and Cu are in excess (Comparative Examples 2 and 4), the improvement in corrosion resistance is limited, but the toughness and weldability are significantly deteriorated, proving the rationality of the upper limit of the composition in this invention.
[0138] When P and S are high (Comparative Example 7), the pitting corrosion sensitivity increases significantly, confirming the enhancement of corrosion resistance by purification smelting.
[0139] 4. Comparison of resistance to hydrogen sulfide stress corrosion cracking (SSRT, under open circuit potential)
[0140]
[0141] Key conclusions:
[0142] The embodiments of the present invention reduce stress corrosion sensitivity by more than 80%, and basically eliminate the risk of brittle fracture in hydrogen sulfide environment;
[0143] Without Nb-V microalloying (Comparative Example 6), the risk of hydrogen-induced cracking increases dramatically, and the stress corrosion sensitivity rises to a high level, verifying the core role of Nb-V hydrogen traps in inhibiting hydrogen-induced cracking.
[0144] When P and S exceed the standard (Comparative Example 7), grain boundaries become the preferred crack propagation path, and stress corrosion susceptibility deteriorates significantly.
[0145] When normalizing was removed (Comparative Example 8), the uneven internal stress and microstructure led to an increase in sensitivity, demonstrating the optimizing effect of the normalizing process on stress corrosion resistance.
[0146] 5. Microstructural Characterization
[0147] 5.1 In Example 1, the microstructure consisted of uniformly fine equiaxed ferrite and diffusely distributed lamellar pearlite, without obvious banding or Widmanstätten structure. The ferrite grains were equiaxed, with an average grain size of 5.5 μm and a narrow grain size distribution (range ≤ 2 μm); the pearlite was diffusely distributed in an island-like pattern, with a lamellar spacing of approximately 0.2~0.3 μm, and no continuous network cementite was present.
[0148] In Comparative Example 6, the microstructure was ferrite + pearlite, but the grains were significantly coarsened. The average grain size of ferrite reached 11.5 μm, and the grain size distribution was uneven, with the largest grain size exceeding 20 μm. The pearlite was distributed in a discontinuous network along the grain boundaries, and the interlamellar spacing increased to 0.4~0.5 μm.
[0149] Due to the lack of pinning effect of nano-precipitates such as NbC and VC, the austenite grains grow abnormally during heating and rolling, resulting in significant coarsening of the microstructure. This is the root cause of the simultaneous decline in its strength, toughness, and resistance to hydrogen-induced cracking.
[0150] In Comparative Example 8, the microstructure consists of deformed ferrite and pearlite, exhibiting obvious rolling deformation texture. The ferrite grains are elongated along the rolling direction, with an average grain size of 7.5 μm. The microstructure has poor uniformity, with pearlite aggregation in local areas and residual rolling internal stress.
[0151] Because it has not undergone normalizing and recrystallization treatment, the deformed structure has not fully recovered and recrystallized, and the internal stress has not been eliminated. This is the main reason for the deterioration of its plasticity and low-temperature toughness and the increase in stress corrosion sensitivity.
[0152] 6. Performance of welded joints
[0153] Simulating on-site railway tunnel construction conditions, manual arc lap welding was performed using E5015 low-hydrogen potassium welding electrodes. No preheating or post-weld heat treatment was performed, and the welding heat input was controlled at 15~20 kJ / cm. System performance tests were conducted on the welded joints, and the results are as follows:
[0154] 6.1. Mechanical Properties
[0155] Tensile properties: The tensile strength of the welded joint is ≥820MPa, the fracture location is located in the base material region, the joint strength coefficient is ≥0.96, which meets the strength requirements of GB 50661 for welded joints of steel structures; there is no weld fracture or brittle fracture of the fusion line.
[0156] Low-temperature impact toughness (-20℃, V-notch): The impact absorption energy of the weld metal is ≥110J, ≥95J at the fusion line, and ≥105J in the coarse-grained zone of the heat-affected zone, all of which are far higher than the engineering requirement of 40J. There is no risk of low-temperature embrittlement, making it suitable for tunnel service environments in high-altitude and cold regions.
[0157] Hardness distribution: weld HV 10 Hardness approximately 210~230, peak hardness in the coarse-grained region of the heat-affected zone ≤245HV 10 The hardness of the base material is approximately 200~210 HV. 10 It has no hard and brittle martensite structure and a gentle hardness gradient, which can effectively avoid hydrogen-induced cracking during welding.
[0158] 6.2. Microstructure of the heat-affected zone
[0159] The heat-affected zone of welding can be divided into a coarse-grained zone, a fine-grained zone, and an incomplete recrystallization zone: the coarse-grained zone consists of fine ferrite and a small amount of pearlite, without coarse Widmanstätten structure; the fine-grained zone undergoes recrystallization due to welding thermal cycling, resulting in even finer grains; and the incomplete recrystallization zone exhibits good structural uniformity.
[0160] Thanks to the low-carbon composition design and the microstructure regulation effect of Ni and Cr elements in this invention, the welding thermal cycle did not cause rapid microstructure deterioration, and there was no obvious softening or embrittlement zone in the welding heat-affected zone.
[0161] 6.3. Resistance to hydrogen sulfide corrosion of welded joints
[0162] After immersion in a simulated tunnel high-hydrogen sulfide environment consistent with the substrate for 60 days, the overall uniform corrosion rate of the welded joint was 0.038 mm / a, and the maximum pitting depth was 0.075 mm, which was only slightly higher than that of the base material (0.032 mm / a, 0.06 mm). There was no preferential corrosion in the weld and heat-affected zone, and the corrosion morphology was consistent with that of the substrate, with no localized groove corrosion.
[0163] The reason is that the Cr, Ni, and Cu elements in the alloy system of this invention do not suffer significant burn-off during the welding process, and a protective rust layer can still be formed at the joint, ensuring the long-term durability of the welded structure.
[0164] 7. Long-term corrosion test
[0165] 7.1. Corrosion performance after 180 days of long-term immersion
[0166] The sample from Example 1 was continuously immersed in a simulated high-hydrogen sulfide tunnel environment for 180 days to test its long-term corrosion performance. The results are as follows:
[0167] The uniform corrosion rate was 0.026 mm / a, which was further reduced compared to the 60-day test value (0.032 mm / a). This reflects the characteristic of the corrosion rate gradually decreasing over time. In the early stage of corrosion, the rust layer gradually forms, and in the later stage, after the dense inner rust layer stabilizes, the corrosion reaction is continuously suppressed, which is consistent with the corrosion evolution law of long-term service.
[0168] Maximum pitting depth: 0.10 mm. The pitting expansion rate slowed down significantly with immersion time, proving that the dense inner rust layer can effectively seal pitting pits and inhibit pitting from developing deeper, supporting the design goal of "100-year durability".
[0169] Based on this long-term corrosion rate, it is estimated that within the design life of 100 years, the uniform corrosion thinning of the steel bars will be about 2.6 mm, and the pitting depth will be about 5 mm. For steel bars with a nominal diameter of ≥12 mm, the remaining cross-section can still meet the load-bearing requirements, which matches the 100-year design life of the tunnel.
[0170] V. Overall Conclusion
[0171] 1. All six embodiments of the present invention simultaneously meet the triple design requirements of high strength, high toughness, and high resistance to hydrogen sulfide stress corrosion, and their performance remains stable and meets the standards within the upper and lower limits of their composition.
[0172] 2. The compositional deviation of the comparative sample verified the critical effect of the Ni-Cr-Cu-Nb-V pentagonal synergistic system. The deficiency of any element will lead to the deterioration of the corresponding performance, while the excess will cause the deterioration of toughness and processability, proving that the compositional range of the present invention is scientific and reasonable.
[0173] 3. Process comparison verified the necessity of the composite process of "purification smelting + two-stage controlled rolling and cooling + 820℃ normalizing". Without normalizing or with insufficient purity, it is impossible to achieve a synergistic match between strength, toughness and corrosion resistance.
[0174] 4. Compared with ordinary steel bars and existing corrosion-resistant steel bars, this invention achieves a significant improvement in stress corrosion resistance and long-term durability; compared with stainless steel steel bars, it meets the requirements of high ground stress and costs only 1 / 5, making it significantly more suitable for engineering applications.
Claims
1. A low-alloy high-strength steel bar for railway tunnels resistant to hydrogen sulfide stress corrosion, comprising the following chemical components by weight percentage: C:0.09%~0.14%; Si: 0.25%~0.40%; Mn: 0.80%~0.90%; P:≤0.015%; S:≤0.010%; Cr:1.95%~2.05%; Ni: 1.45%~1.55%; Cu: 0.20%~0.30%; V:0.07%~0.08%; Nb: 0.04%~0.06%; Al:0.02%~0.05%; The balance consists of Fe and unavoidable impurities.
2. The low-alloy high-strength steel reinforcement for railway tunnels resistant to hydrogen sulfide stress corrosion according to claim 1, wherein, The content of C is 0.10%~0.13%, more preferably 0.11%~0.12%.
3. The low-alloy high-strength steel reinforcement for railway tunnels resistant to hydrogen sulfide stress corrosion as described in claim 1 or 2, wherein, The Ni content is 1.48%~1.52%.
4. The low-alloy high-strength steel reinforcement for railway tunnels resistant to hydrogen sulfide stress corrosion according to any one of claims 1 to 3, wherein, The Cr content is 1.98%~2.02%.
5. The low-alloy high-strength steel reinforcement for railway tunnels resistant to hydrogen sulfide stress corrosion according to any one of claims 1 to 4, wherein, The low-alloy high-strength steel bars for railway tunnels that are resistant to hydrogen sulfide stress corrosion have a uniform and fine ferrite-pearlite structure, wherein the average grain size of ferrite is 4 to 8 μm, the volume fraction of ferrite is 80% to 88%, and the remainder is dispersed lamellar pearlite. More preferably, the average ferrite grain size is 5–6 μm, and the ferrite volume fraction is 83%–85%; Preferably, the microstructure is obtained through controlled rolling and cooling followed by normalizing. Preferably, the reinforcing bars are used in shotcrete support, lining structures, or anchor support systems in railway tunnels with high hydrogen sulfide environments (H2S concentration ≥ 1000 ppm).
6. A method for preparing a low-alloy high-strength steel bar for railway tunnels resistant to hydrogen sulfide stress corrosion, as described in any one of claims 1 to 5, the method comprising the following steps performed sequentially: (1) Purification smelting process; (2) Continuous casting process; (3) Controlled rolling and controlled cooling process; (4) Normalizing heat treatment process.
7. The preparation method according to claim 6, wherein, The purification smelting process includes: Hot metal pretreatment: Desulfurization and dephosphorization processes are adopted to ensure that S ≤ 0.005% and P ≤ 0.010% in the hot metal; Converter steelmaking: final control C ≥ 0.06% to avoid over-oxidation, slag-blocking tapping is adopted, and slag layer thickness ≤ 50mm; LF furnace refining: white slag holding time ≥15min, adjust alloy element composition to the target range; RH vacuum degassing: vacuum degree ≤67Pa, holding time ≥10min, so that [H]≤1.5ppm, [O]≤20ppm, and [N]≤40ppm in steel.
8. The preparation method according to claim 6 or 7, wherein, In the continuous casting process, full-process protective pouring is adopted to prevent secondary oxidation; electromagnetic stirring in the crystallizer and electromagnetic stirring at the end are used; the cross-section of the billet is 150mm×150mm; the casting speed is 2.0~2.5m / min; the secondary cooling zone adopts a weak cooling process; and the specific water content is 0.8~1.0L / kg.
9. The preparation method according to any one of claims 6 to 8, wherein, The controlled rolling and controlled cooling process includes: The steel billet is heated to 1150–1200℃ and held for 1.5–2.0 hours. The rolling process employs a two-stage controlled rolling process: roughing and finishing. In the roughing stage, the initial rolling temperature is 1050–1100℃, the final rolling temperature is 950–1000℃, and the cumulative reduction rate is ≥60%. In the finishing stage, the initial rolling temperature is 850–900℃, the final rolling temperature is 800–850℃, and the cumulative reduction rate is ≥70%. After rolling, controlled cooling is performed using water cooling at a rate of 10–15 °C / s, with a final cooling temperature of 600–650 °C, followed by air cooling to room temperature.
10. The preparation method according to any one of claims 6 to 9, wherein, In the normalizing heat treatment process, the heating temperature is 820±10℃, the holding time is 1h, and the holding time is increased by 0.5h for every 10mm increase in the diameter of the steel bar. The heating rate is <50℃ / h. After being taken out of the furnace, the steel bar is air-cooled to room temperature.
Citation Information
Patent Citations
Chloride ion corrosion resistant hot rolled ribbed bar HRB500cE and processing technology
CN119685722A